The relationship between engaging in adapted competitive physical activity and achievement motivation among physically disabled athletes - firem, tayeb (sports creativity, 2025)
This study aims to determine the role of adapted competitive sports activities in enhancing the achievement motivation of physically disabled athletes through their participation in these activities within sports clubs. The researcher employed a descriptive-analytical approach and utilized the Kenyon Attitudes Towards Physical Activity and Sports scale to refine and refine the data collected through this questionnaire and the Achievement Motivation Scale developed by Joe Wills and translated by Mohammed Hassan Alawi. The study sample consisted of 50 physically disabled athletes distributed across five clubs. In conclusion, this study found that adapted competitive sports activities play a significant and effective role in enhancing the achievement motivation of physically disabled athletes.